Nanostructured Materials for the Detection of Latent Fingermarks - Shahbazi, Sorour (Curtin University, 2020)
Latent fingermarks remain important in criminal cases and detection is essential to their successful use. This thesis describes the application of nanotechnology to overcoming the lack of contrast between latent fingermarks and colourful or fluorescent surfaces. Novel luminescent nanoparticles were successfully applied to the detection of latent fingermarks on highly patterned non-porous surfaces. The significance of the shape of nanoparticles on the quality of the developed fingermarks was also demonstrated for the first time.